Novel Resonance Manipulation Method in Coupled Resonators Using 'Coupling Structure Technique' for Quantum Coherence Effect and Optical Communication Applications (Invited) - Dingel, Benjamin (Archīum Ateneo, 2023)
Recently, we reported a general technique that uses a 'cross-coupling structure' as a new vehicle to manipulate the resonance features of the coupled resonators. The technique is important for the (i) search for new optical analogues of Quantum Coherence Effects (QCEs) and (ii) generation of fresh and richer optical behaviors of the coupled resonators that could open future applications in optical fiber communication. Here, we review two new configurations based on this technique. The first configuration uses a modified standard double resonator (SDR) which we refer to as Cross-coupled SDR (CC-SDR). It is a new analogue circuit of QCE that generates a new QC phenomenon we call Cross-coupled Resonator Induced Shifted Absorption (CRISA). It is the first-time a cross-coupled structure has been suggested in studying QCE. Its core mechanism is due to its 'cross-coupling structure'. Second, we present a modified coupled ring reflector (CRR) configuration where its original directional couplers (DCs) are replaced with cross-coupler(s) to connect the two ring resonators. We refer to it as crisscrossed-assisted CRR (or X-CCR). We review the unique characteristics of these two configurations and discuss their applications as optical devices.